A novel laparoscopic assisted mediastinal dissection with gastric tube inversion technique for gastric tube cancer reconstructed through a retrosternal route. Issue 5 (24th May 2021) - Abe, Tetsuya; Numata, Yoshihisa; Higaki, Eiji; Hosoi, Takahiro; Shimizu, Yasuhiro
Abstract: A median sternotomy is often performed in patients with gastric tube cancer reconstructed through the retrosternal route; however, this procedure is invasive and has the risk of severe infectious complications. To overcome these problems, we created a novel method to perform the reconstructed gastric tube resection using a gastric tube inversion technique combined with a laparoscopic mediastinal approach. After the duodenum was divided, the oral side of the cut end was sutured with silken threads for traction. The gastric tube was dissected from the caudal side under a laparoscopic mediastinal approach, whereas the cervical esophagus was taped. After the adhesion between the middle side of the posterior sternum and the reconstructed gastric tube was dissected to the cervix, the gastric tube was inverted by guiding and pulling the thread toward the cervical side. Sharp dissection was facilitated between the inverted gastric tube and the surrounding organs under moderate traction and a favorable surgical view. We have performed this procedure and evaluated the short‐term outcomes in six cases. The laparoscopic mediastinal approach was completed without a median sternotomy in all six cases. Restorable intraoperative lung injury was observed in one case and no major vessel injuries were observed. The postoperative course was satisfactory with a 29.5‐day median length of hospital stay (range, 16‐60 days). The gastric tube inversion technique combined with the laparoscopic mediastinal approach for patients with retrosternal‐reconstructed gastric tube cancer was shown to be safe and less invasive and should be considered in resection of the reconstructed gastric tube. Abstract : We created the novel gastric tube inversion technique combined with laparoscopic mediastinal approach in gastric tube resection for the gastric tube cancer reconstructed through the retrosternal route. This approach is less invasive and safe, thereby avoiding the risk of serious complication associated with median sternotomy. Moreover, the gastric tube inversion technique helped to secure a sufficient working space in a narrow operation field and allows for safe dissection under favorable surgical view.